PENATAAN PERMUKIMAN KUMUH TERINTEGRASI DI KOTA SEMARANG - Risky Yustiani P; Retnayu Prasetyanti; Hamidah Rosidanti S (The Indonesian Journal of Public Administration (IJPA), 2021)
ABSTRACT, The concentration of the population in urban areas, the number of decent housing that does not meet the needs, and the economic gap creates slum settlements that give rise to social, health problems and damage the aesthetics of urban planning. With the issuance of Law no. 1 of 2011 the government targets to increase the number of decent and healthy settlements, especially for 30 priority cities/regencies in Indonesia. This policy is in line with the implementation of the Sustainable Development Goals program on poverty, inequality and sustainable cities and communities. As one of the priority areas, the city of Semarang has succeeded in conjuring the face of the slums. This study tries to present an analysis related to the practice of structuring slums through a case study in Randusari Village. The main aspects analyzed are the form of integration, coordination, participation, and the model of slum settlement arrangement. This study uses a qualitative approach with descriptive research methods that combine literature review research techniques and secondary data. The results of the study explain that the KOTAKU program helps the government in overcoming the problem of slum settlements and the welfare of the local community. The thematic village and rainbow village schemes that are implemented have interrelated objectives, namely 4E (ethos, ecosystem, education and economy). The success of the top-down bottom-up policy model in this program is carried out with community participation from the planning to evaluation stages so as to create sustainable innovation in residential areas, either in cooperation or delegation of power.Keywords: Slums, Integration, Coordination, Participation  ABSTRAK, Terpusatnya penduduk di wilayah perkotaan, jumlah hunian layak yang belum mencukupi kebutuhan, dan gap  ekonomi menciptakan pemukiman kumuh yang melahirkan masalah sosial, kesehatan dan merusak estetika penataan kota. Dengan terbitnya UU No. 1 tahun 2011 pemerintah menargetkan peningkatan jumlah permukiman layak dan sehat terutama untuk 30 Kota/Kabupaten prioritas di Indonesia. Kebijakan ini senada dengan implementasi program Sustainable Develeopment Goals tentang kemiskinan, ketidaksetaraan serta kota dan komunitas berkelanjutan. Sebagai salah satu daerah prioritas, Kota Semarang berhasil menyulap wajah permukiman kumuh tersebut. Penelitian ini berusaha menyajikan analisis terkait praktik penataan permukiman kumuh melalui studi kasus di Kelurahan Randusari. Aspek utama yang dianalisis adalah bentuk integrasi, koordinasi, partisipasi, serta model penataan permukiman kumuh.  Penelitian ini menggunakan pendekatan kualitatif dengan metode penelitian deskriptif yang mengkombinasikan tenik penelitian literature review dan data sekunder. Hasil penelitian menjelaskan bahwa program KOTAKU membantu pemerintah dalam mengatasi masalah permukiman kumuh dan kesejahtraan masyarakat setempat. Skema kampung tematik dan kampung pelangi  yang diterapkan mempunyai tujuan yang saling berkaitan satu dan yang lainnya yaitu 4E (etos, ekosistem, edukasi dan ekonomi). Keberhasilan model kebijakan top-down bottom-up pada program ini terselenggara dengan keikutsertaan masyarakat mulai dari tahapan perencanaan hingga evaluasi sehingga menciptakan inovasi berkelanjutan di lingkungan pemukiman baik dalam kerjasama atau pendelegasian kekuasaan.Kata kunci: Pemukiman Kumuh, Integrasi, Koordinasi, Partisipasi